The kite runner as a bildungsroman of emotional maturation with the intergration of father-son relationships. - Tan, Renjie (2011)
“Rahim Khan had summoned me here to atone not just for my sins but for Baba’s too.” Thus are the words by Amir, the protagonist in The Kite Runner. Written by Khaled Hosseini, an Afghani writer living in the United States, the novel is about a young boy, Amir and the life changing experiences he had living in Afghanistan in her days of peace and moving to the United States during the war. The purpose of this study is to look at how this novel fares as a Bildungsroman of emotional maturation with psychological analysis to identify the father-son relationships that the author has weaved into it. This research is done in the qualitative method, using genre studies, character analysis and psychological criticisms to gather and analyze the novel. The results are drawn from examples in the novel, using the character’s words and experiences to back up the IDEAL, father wound and fatherhood evaluation theories that are illustrated in the literature review. This research paper is aimed to increase the appreciation and love of this beautifully written novel that talks about love, anger, forgiveness and ultimately, redemption.